MedOANet: The Copyright and OA Landscape in Mediterranean Europe - Ludewig, Karin (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2014)
The aim of this paper is to present existing copyright policies of major stakeholders of scholarly communication in Mediterranean countries and to discuss whether these copyright policies need to be improved and by which measures. In order to do so, this paper firstly introduces MedOANet, which is an EU-funded project whose aim is to enhance existing national policies, strategies and structures for OA and to contribute towards the implementation of new ones in Mediterranean countries, namely France, Greece, Italy, Portugal, Spain and Turkey. Secondly, this paper gives an overview of the results of a survey which was conducted in 2012 amongst research publishers by MedOANet. Thirdly, an interpretation of the most striking results of the survey is given: research publishers based in Mediterranean countries have, on average, very OA-friendly copyright and self-archiving policies in place. Some improvements could be achieved by developing an OA-conducive campaign of awareness raising; additionally, the author of the article suggests that national policy-makers support OA as the default method of scholarly communication by introducing legal provisions into copyright law that enable researchers to go for a Green Road publication independently of prior assignment of exploitation rights to publishers.